Balinese Food Menu in Translation - Agus Darma Yoga Pratama (Jurnal Kajian Bali (Journal of Bali Studies), 2023)
Translation plays an important role in transferring the data among languages. Thus, translation is not just about translating languages, but also exploring cultures. This can be seen from the translation of traditional Balinese food menus which used to present various names of special dishes as part of Balinese local wisdom. The translation of traditional Balinese food menus is interesting to study since there are no professional translators involved in making it and the emergence of various technical terms are not easy to translate. This research was conducted with a qualitative descriptive method to analyze data and determine the translation strategy by considering the aspects of ingredients, taste, size, process, and shape. The theoretical framework by Newmark (1988) was applied to examine the data. The results of the analysis show that the food menu translation strategy which includes expansion and descriptive equivalent are based on several aspects of food menu translation.